Inhibitory response of Pectobacterium carotovorum subsp. carotovorum(Jones) Dye Applied with Betel Leaf and Areca Nut Extract as a Potential Organic Bactericide - Emerensiana - Uge; Titik Sri Harini; Sri Widinugraheni; Jilinda B.D Henuk (Cannarium, 2020)
Soft root caused by the bacterium Pectobacterium carotovorum subsp carotovorum (Jones) Dye (P.c.c), is a disease that is very detrimental to horticultural plants, especially carrot. The disease control is commonly done by chemical techniques, but because of the negative impact, it is important to choose an environmentally friendly techniques, such as plant extracts. The aim of this research is to know response of P.c.c bacteria growth when it is applied with betel leaves extracts (BTL) and Areca nut extracts (ANE) in different concentrations.This research is begun with pathogenecity test, Gram coloring test, and Growing on selective media. While the inhibation testing was carried out in In Vitro. Experiment were carried out with agarose-wells method, where bacterial inoculum was grown with agarose medium, then plant extract added in to medium through the well. The observation done by measured inhibitory zone diameter (mm) around agarose-wells. The data presented the size of the inhibitory zone diameter (mm) formed on P.c.c culture media, then was analyzed using ANOVA followed by Duncan’s test.Pathogenecity test, Gram-coloring test, and growing selective media test showed that there was symptoms on 4 days after infection, red and rod-shaped bacteria, while in CVD medium, the bacteria grow uniformly at 37 0 C, although they do not form a basin in the medium. And In vitro test showed that the treatment of BTL, and ANE at 10%, 5%, and 10% concentration respectively, had good ability to inhibit bacteria in NA medium, with the average inhibition zone diameters of 32.33 mm, 28.67 mm, and 33 .67 mm.